Wage Implications at EU Level - Miron Dumitrescu; Magda Alina Manole; Luminita Leocadia Sarbu (Hyperion Economic Journal, 2013)
In all conditions of time and space, economic activity necessarily involves active work as a determinant factor of production and beneficiary of its results. In the market economy, labor services are provided to production, as with the other factors of production, through market transactions. This article aims labor factor, the role and characteristics of labor as a production factor and the employment in the EU. As a secondary market, labor market is influenced by other markets and generates, in turn, effects that are found in all other structures of the market economy system